2012
DOI: 10.1111/j.1365-2435.2012.02009.x
|View full text |Cite
|
Sign up to set email alerts
|

Flower movement increases pollinator preference for flowers with better grip

Abstract: Summary1. Conical cells in the petal epidermis are common across many diverse flowering plant species, and it was recently shown that in difficult-to-handle flowers, pollinators prefer conical cells because they increase grip. However, this does not explain the prevalence of conical cells amongst other, simpler, flowers. 2. The movement of objects is an integral part of the world and is of particular importance to bees because the relative motion of objects is essential to a bee's 3D vision. The motion of flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…We have not found a relationship between elevation and papillate anthers, and the character is polymorphic in several species (e.g., Solanum madagascariense , Solanum terminale ). Glover et al (2004) induced the formation of papillae (trichomes) in Solanum dulcamara by overexpression of MIXTA and MIXTA-like genes; these transcription factors are responsible for the conical cells of petals that function in both pollinator attraction (Noda et al 1994) and grip (e.g., Alcorn et al 2012). Current work (B.J.…”
Section: Taxonomy Of the African Non-spiny (Ans) Cladementioning
confidence: 99%
“…We have not found a relationship between elevation and papillate anthers, and the character is polymorphic in several species (e.g., Solanum madagascariense , Solanum terminale ). Glover et al (2004) induced the formation of papillae (trichomes) in Solanum dulcamara by overexpression of MIXTA and MIXTA-like genes; these transcription factors are responsible for the conical cells of petals that function in both pollinator attraction (Noda et al 1994) and grip (e.g., Alcorn et al 2012). Current work (B.J.…”
Section: Taxonomy Of the African Non-spiny (Ans) Cladementioning
confidence: 99%
“…Texture in petals and other floral parts may offer both visual and tactile cues to visitors (Kevan and Lane 1985;Whitney et al 2011;Alcorn et al 2012). Whitney et al (2011), reviewed the importance of conical petal epidermal cells to enhance pollination success and concluded that conical epidermal cells significantly increased tactile handling of the flower by pollinators and hence their preference.…”
Section: General Approach Advertisement and Discoverymentioning
confidence: 99%
“…Furthermore, recent studies have revealed that most flowers have conical (papillate) epidermal cells, which facilitate pollinators gripping the flowers on petal surfaces (Kevan & Lane ; Whitney et al . ; Alcon, Whitney & Glover ).…”
Section: Introductionmentioning
confidence: 99%